Incidencia de las propiedades físico-químico de los suelos vertisoles en la producción de cultivos de la costa ecuatoriana - Tomala Avila, Juliana Madelein (2024)
The research addressed the topic of incidence of the physical-chemical properties of vertisol soils in the production of crops on the Ecuadorian coast in order to identify how to work in these soils. The main objective of this research is to establish the incidence of the physical-chemical properties of vertisol soils in their agronomic capacity, this because in order to be able to grow in this type of soil, several factors have to be taken into account, their texture, their density, the area in which they are found, the nutrients that the soil has and those that it lacks since this is fundamental when making a plantation, in addition to focusing on what are the main characteristics of these soils and establishing an adequate management for them where we recognized that there are adequate management practices for these soils, for example in these soils you must have good drainage because they suffer a lot from water waterlogging, crop rotation is another important factor for the soils to recover after a harvest. In conclusion, with the different criteria and opinions of several authors, it can be said that the characteristics of vertisol soils are of great importance, soil analysis must be carried out before any agricultural work and the crop that we are going to have in this type of soil must be known very well, to avoid future losses.